Biopolymer Production Kinetics of Mixed Culture Using Wastewater Sludge as a Raw Material and the Effect of Different Cations on Biopolymer Applications in Water and Wastewater Treatment. (1st May 2016) - More, T. T.; Yan, S.; Tyagi, R. D.; Surampalli, R. Y.
ABSTRACT: : Thirteen extracellular polymeric substances (EPS) producing bacterial strains were cultivated (as mixed culture) in the sterilized sludge (suspended solids of 25 g/L) and the batch fermentation was carried out. Mixed culture revealed a high specific growth rate of 0.35/hr. The EPS production rate was higher up to 24 hours, which gradually decreased with further incubation. The kinetic estimates demonstrated growth‐associated EPS production. Broth EPS revealed higher flocculation activity when combined with different cations (Ca 2+, Mg 2+, Fe 3+, and Al 3+ ) in river water (≥90%), municipal wastewater (≥90%), and brewery wastewater (≥80%), respectively. A low dose (5 to 40 mg/L) of trivalent cations was required to achieve higher flocculation compared to the divalent cations (50 to 250 mg/L). Flocculation performance of EPS was comparable to Magnafloc‐155 (chemical polymer) and, hence, it could be used as a flocculant.